The performance and importance of the dental surgeon in an Intensive Care Unit (Research, Society and Development, 2021)
Oral hygiene deficiency is common in intensive care unit (ICU) patients, which potentiates biofilm colonization by microorganisms that lead to respiratory infections. The literature has been reporting the association between oral health and systemic diseases, especially the development of ventilator-associated pneumonia (VAP). The objective of this study is to shed light on the performance and importance of the dental surgeon in an ICU. This is an integrative review performed in the PubMed database. It was adopted as the inclusion criteria papers in Portuguese or English, available as full-text papers, published from 2016 to 2021, and that answer the guiding question: what is the professional performance and importance of a dental surgeon in an ICU? After reading the title and abstract, 8 articles that reported the relationship between oral health and systemic disease were selected, especially regarding the development of VAP. Through this review we conclude how much it is indispensable the presence of a dental surgeon as part of an ICU multidisciplinary team, ensuring that the patient will be treated in an integral way and have their quality of life improved.